(untitled) (Altre Modernità, 2019)
The linguistic complexity of the Caribbean context forces any literary author to choose a language (or more languages) in the very wide range offered by the Creole continuum, from Creole to the European languages that arrived on the islands through colonization. The situation of Creole in the French Antilles is particularly interesting, because it reveals the history of a denied or silenced language, at times by its own speakers, and also by the great authors of the Francophone Caribbean, as we will see analyzing the relationship with Creole and French of authors of different generations, from Césaire and Glissant to Confiant and Chamoiseau. Instead of judging these authors and their linguistic choices, this article will focus on a reading of their complex and sometimes ambiguous relationship with these two languages, and on the influence that this has had on the birth of a literature in Creole in Martinique. Reading this relationship through their interviews, with the characteristic immediacy and spontaneity of this genre, will help us to read an unstable thought, revealing not only the results of their reflection on the possibilities of a single language, but above all the possibility of using this history of oppression as a starting point for a new perception of the role that any language can play in Caribbean literary creation.